Identification of the financial potential of the franchised tourist network: gnoseological discourse - S.V. Bardash; О.М. Petruk (Економіка, управління та адміністрування, 2021)
The article is devoted to the study of the nature and composition of the financial potential of the franchised tourist network, which will contribute to the development of methodological support for the formation of indicators and criteria for analyzing financial potential as a prerequisite for assessing the likelihood of overcoming the crisis, which are facing tourism businesses during the pandemic. It is determined that today the research is being done on the concept of «financial potential», the search for methods of its evaluation, as well as the disclosure of management features. To reveal its essence, resource or support, effective, reserve, effective-reserve, resource-reserve, resource-effective, complex approaches are used. A large number of approaches indicate that the scientific community is actively trying to find the truth. The lack of a universal approach to determining the nature and composition of financial potential does not allow to form adequate methods of its evaluation and further effective use, and the only criterion for the correct application of an approach is its widespread recognition through practice. Thus, the research in this direction is relevant and promising. The aim of the article is to analyze scientific approaches to the essence of the concept of «financial potential» as a basis for developing methodological approaches to determining the financial potential of franchised tourist networks. As a result of morphological analysis, it was concluded that financial potential should be understood as a set of financial assets that are monetary at the beginning of the financial year and can be monetized during this period, as well as non-operating non-current assets, the sale of which increases financial opportunities according to the tasks of implementation of the economic strategy of the business entity. The applied application of the proposed scientific and methodological approach will create opportunities to overcome the unprofitable position of franchised tourist networks, which is possible due to the full identification of its financial potential. Franchising itself is an important tool for small business development and one of the most modern models of organization and implementation of entrepreneurial activity, because doing business on such a model solves a number of current problems of small business, the main of which are limited material, financial, labor, and information resources.